The Gothic in Eastern Literature (Kurdish and Persian) with Reference to Death of the Second Single Child and Prince Ehtejab - Bahar Kazemi; Badrieh Ghavami (پژوهشنامه ادبیات کردی)
The Gothic style was a mode of story writing which became popular in the eighteenth and the beginning of the nineteenth century in Europe when suppression caused by church and religious beliefs on the people was dominant. These stories are created based on imaginary and unreal situations. The role of gothic writers is to analyze the psychological disorders; therefore, novels written in the gothic style are also known as black romance. In Eastern literature (Kurdish and Persian), some socio-political events encouraged story writers to go for surrealism and magical realism adapted with social infrastructure of their community. In this research, Gothic elements in Hoshang Golshiri’s Prince Ehtejab and Bakhtiar Ali’s Death of the Second Single Child have been explored through their relevance to Iranian and Kurdish society. Moreover, the style of both authors has also been investigated. The results indicate that Hoshang Golshiri and Bakhtiar Ali have used Gothic techniques in their stories in accordance with the social conditions of their society. The Gothic is a means to reflect the social and political conditions of these authors' era, where tensions caused by social issues in turn, yields to socio-political situation of their era in a Gothic format.